Trypanosoma cruzi strains from triatomine collected in Bahia and Rio Grande do Sul, Brazil - Aline Rimoldi Ribeiro; Vagner José Mendonça; Renata Tomé Alves; Isabel Martinez; Renato Freitas de Araújo; Fernanda Mello; João Aristeu da Rosa (Universidade de São Paulo, 2014)
OBJECTIVE Collection of triatomines in domestic, peridomestic and sylvatic environments in states of Bahia and Rio Grande do Sul, Northeastern and Southern Brazil respectively, and isolation of Trypanosoma cruzi strains. METHODS First, the captured triatomines were identified using insect identification keys, then their intestinal content was examined by abdominal compression, and the samples containing trypanosomatid forms were inoculated in LIT medium and Swiss mice. RESULTS Six triatomine species were collected in cities in Bahia, namely Panstrongylus geniculatus (01), Triatoma melanocephala (11), T. lenti (94), T. pseudomaculata (02), T. sherlocki (26) and T. sordida (460), and two in cities in Rio Grande do Sul, namely T. circummaculata (11) and T. rubrovaria (115). Out of the specimens examined, T. cruzi was isolated from 28 triatomine divided into four different species: T. melanocephala (one), T. lenti (one), T. rubrovaria (16) and T. sordida (10). Their index of natural infection by T. cruzi was 6.4%. CONCLUSIONS The isolation of T. cruzi strains from triatomines found in domestic and peridomestic areas shows the potential risk of transmission of Chagas disease in the studied cities. The maintenance of those T. cruzi strains in laboratory is intended to promote studies that facilitate the understanding of the parasite-vector-host relationship.